Iran’s nuclear program, 1979-2015: A study in nuclear proliferation and rollback / Farhad Rezaei - Farhad , Rezaei (2016)
This study constitutes the first full and systematic account of Iran’s nuclear program since the Islamic Revolution in 1979 analyzed within the context of proliferation, rollback and sanction theories. Extant literature suffers from polarization; some scholars embrace the neorealist postulation that proliferators are rational actors and, by extension, when overwhelmed by sanctions, they would respond in a rational way and embrace rollback. Others contend that neorealist rationality cannot be applied to new proliferators of the Second Nuclear Age, notably Iran. The goal of the study is to find out whether Iran fits the profile of a rational proliferator and as such, is likely to respond to sanctions in a rational way. Two questions central to this inquiry are: whether Iran followed the neorealist precepts of proliferation and whether the increasingly punitive sanctions imposed by the intentional community caused it to reevaluate the cost of the nuclear program. The detailed research based primarily on Farsi language sources indicates that Iran can be described as a rational proliferator; seared by the war with Iraq, its leaders decided that a nuclear capability would provide protection from predatory neighbors as well as shield it from the United States. The relative ease of access to nuclear technology and the weak penalties for proliferation reinforced Tehran’s conviction that the cost of running the program was low and manageable. When faced with harsh sanctions that increased the price tag of the nuclear program to a level deemed catastrophic to the economy, the regime embarked upon an unprecedented open debate on the cost-benefits of the program. The debate has been complicated by structural segmentation of the political system. But there is a growing recognition among key elites to embrace a rollback in order to obtain sanctions relief and indeed, reintegrate into the community of nations.